A New Coupled Fractional Reduced Differential Transform Method for the Numerical Solutions of (2+1)-Dimensional Time Fractional Coupled Burger Equations. (13th May 2014) - Ray, S. Saha
Abstract : A very new technique, coupled fractional reduced differential transform, has been implemented to obtain the numerical approximate solution of (2 + 1)-dimensional coupled time fractional burger equations. The fractional derivatives are described in the Caputo sense. By using the present method we can solve many linear and nonlinear coupled fractional differential equations. The obtained results are compared with the exact solutions. Numerical solutions are presented graphically to show the reliability and efficiency of the method.